Identifying Key Factors of Consumer Behaviour in an Online Environment: a Study of Taiwan Online Consumers - Chen, Mei-Ling (2008)
Consumer behaviour in an online environment has been drawn much attention in different perspectives and different countries. However, there is little research conducted culture differences, so it is doubtful that the uniform market strategy is applicable in Taiwan online market. This project considers the implication of variables in consumer behaviour and focuses on CDP model which can be used as a good start point to investigate consumer behaviour. Reports of key factors already carried out in Taiwan are examined and the most important findings are highlighted. With regard to key variables influence decision process, it is concluded that consumers consider more quality, brand, and the design of the cyberspace which affect their intention toward online purchasing rather than price issue. This may be of interest to marketers, especially in Chinese online market which tend to upgrade or apply electronic commerce.